Pemberdayaan Masyarakat dalam Pembentukan Usaha Kecil, Mikro dan Menengah Produk Serundeng Kerang di Gampong Alue Dua Muka O Kabupaten Aceh Timur - Zulfiani, Zulfiani; Suriyani, Meta; Asyiah, Nur; Fitriani, Rini (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
Gampong Alue Dua Muka O, Idi Rayeuk District, East Aceh Regency is a coastal area, where the people work as fishermen who produce a lot of marine products, one of which is shellfish. Shellfish are sold raw directly to local markets, innovation has not yet been made into a processed food product, namely shellfish serundeng, which can be marketed widely. This is due to limited public knowledge of the processed food product shellfish serundeng (Sukera). The partner group comes from a group of PKK mothers who want to become new entrepreneurs. Community service to introduce shell serundeng (Sukera) as a product that can be developed and marketed and has the potential to increase community income. This community service has supported partner groups in Alue Dua Muka O Village to produce shell serundeng products, and understand product licensing, packaging design, copyright, business governance and marketing.